066 Haemospermia in the Real-Life Setting: Challenging the EAU Guidelines. (1st May 2022) - Pozzi, E.; Ventimiglia, E.; Fallara, G.; Boeri, L.; Belladelli, F.; Cignoli, D.; Candela, L.; Capogrosso, P.; Schifano, N.; Raffo, M.; Colandrea, G.; Cornelius, J.; et al.
ABSTRACT: Introduction: The Sexual and Reproductive Health guidelines of the European Association of Urology (EAU) suggest stratifying patients complaining of haemospermia into low versus high-risk categories for treatable aetiologies. Objective: To validate EAU guidelines in a homogeneous cohort of men with haemospermia and to identify a novel and better performing risk stratification compared to EAU guidelines. Methods: Data from 283 consecutive patients complaining of a single episode/recurrent haemospermia were retrospectively analysed. Patients were stratified into low vs. high-risk according to EAU guidelines, whose diagnostic performance was then validated. We identified a new risk stratification model based on clinical factors associated with i) positive semen culture and ii) prostate cancer (PCa) and bladder cancer (BC). Diagnostic accuracy of the two predictive models (EAU vs. New) was assessed and decision curve analyses (DCA) tested their clinical benefit. Results: Overall, 259 (91.5%) were high-risk and 24 (8.5%) low risk according to the EAU guidelines. Recurrent haemospermia was reported by 134 (47.4%) patients. 126 (44.5%) had baseline CCI score ≥ 1. At MVA logistic regression analysis, history of recurrent genito – urinary tract infections was identified as a predictor for positive semen culture (OR: 3.39, 95% CI: 1.77 – 6.57, p=0.002). Likewise, baseline CCI ≥ 1 was identified as a predictor for PCa and BC (OR: 1.55, 95% CI: 1.17 – 2.04, p=0.009). Sensitivity, specificity, and AUC of the EAU guidelines were 13.3%, 89.2% and 51% respectively, whereas the new model performed substantially better: 98.9%, 58% and 78% respectively. Conclusion: The application of the EAU risk stratification does not ensure proper identification of high-risk patients complaining of haemospermia. We propose a novel, better performing and easily implementable risk stratification. Disclosure: Work supported by industry: no.